A Novel Technique That Protects the Lips during Orthognathic Surgery. Issue 11 (November 2016) - Kamochi, Hideaki; Sugawara, Yasushi; Uda, Hirokazu; Sarukawa, Shunji; Sunaga, Ataru; Yoshimura, Kotaro
Abstract : Summary: Serious lip injuries can occur during orthognathic surgery. Although an Angle Wider device, which is commonly used during orthognathic surgery, provides some lip protection, it leaves more than half of the lip exposed to surgical instruments. Here, we describe a novel technique to protect the entire upper and lower lips during orthognathic surgery using a minilaparotomy wound edge protector (Lap-Protector). We used this method in 60 patients who have undergone orthognathic surgeries such as sagittal split ramus osteotomy and Le Fort I osteotomy since 2009, and no lip injuries have occurred. Although this technique can be somewhat challenging at first and creates some difficulty in exposing the surgical field on the lateral side, we believe that using a wound edge protector minimizes the risk of lip injury during orthognathic surgery. Abstract : Supplemental Digital Content is available in the text.